A RARE CASE OF SUCCESSFUL COMPLETION OF HETEROTOPIC PREGNANCY WITH FAILED TUBAL MISTARRIAGE - Гребенникова, Эльвира Константиновна; Цхай, Виталий Борисович; Гребенникова, Эльвира Константиновна; Домрачева, Марина Яковлевна; Янин, Вадим Николаевич; Андреева, Алла Андреевна (Mother and Baby in Kuzbass, 2024)
In connection with the widespread introduction of assisted reproductive technologies, there has recently been a trend towards a significant increase in heterotopic pregnancy (HP), in which the coexistence of intrauterine and ectopic pregnancy is observed.Recently, publications have appeared in the foreign literature that are reports on clinical cases of HD, describing a combination of intrauterine and tubal pregnancy, intrauterine and ovarian pregnancy, as well as intrauterine and cervical pregnancy. We did not find such publications in the domestic literature.
Keywords: heterotopic pregnancy; failed tubal miscarriage; ectopic pregnancy; intrauterine pregnancy